Triple oxygen isotope distribution in modern mammal teeth and potential geologic applications. (15th August 2022) - Lehmann, Sophie B.; Levin, Naomi E.; Passey, Benjamin H.; Hu, Huanting; Cerling, Thure E.; Miller, Joshua H.; Arppe, Laura; Beverly, Emily J.; Hoppe, Kathryn A.; Huth, Tyler E.; Kelson, Julia R.; Luyt, Julie; et al.
Abstract: Reconstructing water availability in terrestrial ecosystems is key to understanding past climate and landscapes, but there are few proxies for aridity that are available for use at terrestrial sites across the Cenozoic. The isotopic composition of tooth enamel is widely used as a paleoenvironmental indicator and recent work suggests the potential for using the triple oxygen isotopic composition of the carbonate component of mammalian tooth enamel (Δ′ 17 Oenamel ) as an indicator of aridity. However, the extent to which Δ′ 17 Oenamel values vary across environments is unknown and there is no framework for evaluating past aridity using Δ′ 17 Oenamel data. Here we present Δ′ 17 Oenamel and δ 18 Oenamel values from 50 extant mammalian herbivores that vary in physiology, behavior, diet, and water-use strategy. Teeth are from sites in Africa, Europe, and North America and represent a range of environments (humid to arid) and latitudes (34°S to 69°N), where mean annual δ 18 O values of meteoric water range from –26.0‰ to 2.2‰ (VSMOW). Δ′ 17 Oenamel values from these sites span 162 per meg (–252 to –90 per meg), where 1 per meg = 0.001‰). The observed variation in Δ′ 17 Oenamel values increases with aridity, forming a wedge-shaped pattern in a plot of aridity index vs. Δ′ 17 Oenamel that persists regardless of geographic region. In contrast, the plot of aridity index vs. δ 18 Oenamel for these same samples does not yield a distinct pattern. We use these new Δ′ 17 Oenamel data from extant teeth to provide guidelines for using Δ′ 17 Oenamel data from fossil teeth to assess and classify the aridity of past environments. Δ′ 17 Oenamel values from the fossil record have the potential to be a widely used proxy for aridity without the limitations inherent to approaches that use δ 18 Oenamel values alone. In addition, the data presented here have implications for how Δ′ 17 Oenamel values of large mammalian herbivores can be used in evaluations of diagenesis and past p CO2 and past gross primary productivity.